2016
DOI: 10.15537/smj.2016.11.15617
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of transthoracic versus transesophageal echocardiography in transcatheter closure of atrial septal defects

Abstract: Objectives:To assess the safety and effectiveness of transthoracic echocardiography (TTE) in monitoring transcatheter closure of atrial septal defect (ASD), in comparison with conventional technique using transesophageal echocardiography (TEE).Methods:A retrospective review of all cases of transcatheter closure of isolated ostium secundum ASDs operated from 2005 to 2015, at the Pediatric Interventional Cardiology Department, King Abdulaziz University Hospital, Jeddah, Kingdom of Saudi Arabia. Exclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Many experts and scholars have demonstrated that, for a skilled operator, transthoracic ultrasound can replace transesophageal ultrasound for atrial and occlusion guidance under certain conditions [ 11 ]. Azhar reported that transthoracic ultrasound is safer than transesophageal ultrasound in the absence of atrial occlusion, leading to a significant reduction in the operating time, radiation exposure time, and application time of basic anesthesia [ 12 ]. Since echocardiography is two-dimensional, it is critical to accurately determine the position of the catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Many experts and scholars have demonstrated that, for a skilled operator, transthoracic ultrasound can replace transesophageal ultrasound for atrial and occlusion guidance under certain conditions [ 11 ]. Azhar reported that transthoracic ultrasound is safer than transesophageal ultrasound in the absence of atrial occlusion, leading to a significant reduction in the operating time, radiation exposure time, and application time of basic anesthesia [ 12 ]. Since echocardiography is two-dimensional, it is critical to accurately determine the position of the catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Many experts had proved that TTE can be used as a reliable tool for the measurement of the diameter of ASD and for guidance during device closure by skilled hands, taking the place of TEE in some circumstances[24]. Azhar reported that TTE had the same efficacy in transcatheter closure of ASD compared with TEE and had superior safety, including a significant reduction of procedural time and fluoroscopy times as well as less use of general anesthesia[25]. Pan et al[26] concluded their experience of using TTE guidance as the only imaging tool for the process of percutaneous ASD closure.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients in the present study underwent ostium secundum atrial septal [5,6,7,18] and limited data is available on transcatheter device closure of ostium secundum atrial septal defect in smaller children (< 15 Kg). The drawback of transesophageal echocardiography is the difficult availability, need for anaesthesia and endotracheal intubation, the morbidity associated, and longer procedural time [19,20].…”
Section: Discussionmentioning
confidence: 99%